Investigating the Effect of Self-Care Training on Life Expectancy and Quality of Life in Patients with Gastrointestinal Cancer under Radiotherapy - Davood Hekmatpou; Azadeh Nasiri; Fatholah Mohaghegh (Elsevier, 2019)
Objective: A huge amount of the efforts made by health teams is dedicated to caring for cancer patients. This study has aimed to investigate the effect of self-care training on life expectancy and quality of life (QOL) in patients with gastrointestinal cancer who were under radiotherapy. Methods: In this clinical trial, 50 patients were selected using the block randomization method. The intervention was performed at Ayatollah Khansari Hospital in Arak, Iran. The patients in the intervention group received three sessions of face-to-face training. The data collection tools included Schneider's Life Expectancy Questionnaire and EORTC QOLQ-C30. Data were analyzed by SPSS version 23. Results: In the control group, 16 were male (64%) and 9 female (36%), and in the intervention group, 14 were male (56%) and 11 were female (44%). Before the intervention, the two groups were homogenous regarding all variables. After the intervention, the mean of QOL was 67 ± 22.62 in the intervention group and 56 ± 18.55 in the control group (P < 0.05). In examining the different dimensions of QOL, improvement in all functional dimensions was observed in the intervention group. After the intervention, the mean score of life expectancy showed a significant difference (P < 0.05) between the intervention group (39.52 ± 5.26) and the control group (31.6 ± 7.13). Conclusions: It was found that self-care training improved the QOL and life expectancy of patients with gastrointestinal cancer who were under radiotherapy. Therefore, self-care training is recommended to improve the QOL and the life expectancy of cancer patients.